Determination of Cadmium in Tap, Sea and Waste Water Samples by Vortex-Assisted Dispersive Liquid-Liquid-Solidified Floating Organic Drop Microextraction and Slotted Quartz Tube FAAS After Complexation with a Imidazole Based Ligand - Findikoglu, Maral Selin; Firat, Merve; Chormey, Dotse Selali; Turak, Fatma; Sahin, Cigdem; Bakirdere, Sezgin (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
This study presents a combination of dispersive liquid-liquid-solidified floating organic drop microextraction (DLLSFODM) and slotted quartz tube (SQT) with conventional flame atomic absorption spectrometry (FAAS) to improve the sensitivity for cadmium determination. A ligand namely 2-(4-methylphenyl)-1H-imidazo-[4,5-f]-[1,10]-phenanthroline which has not been used in trace analyte determination was used to form a cadmium complex. Stepwise optimization of parameters affecting complex formation (pH, ligand, and buffer solution) and extraction (extraction and dispersive solvents, salt effect and mixing) was done to maximize cadmium absorbance. The slotted quartz tube was fitted onto the flame burner and optimized to increase residence time of atoms in the flame. Instrumental parameters such as sample and fuel flow rate were also optimized to further enhance the absorbance signal for cadmium. Using optimal parameters and values, the limits of detection and quantification were determined to be 0.81 and 2.69 mu g L-1, respectively. Low percent relative standard deviations (< 6.0%) indicated good precision for both extraction and instrumental measurements. Recovery tests were used to determine the accuracy of the method and the recovery results obtained were between 88 and 113%.
Keywords: Cadmium; Flame atomic absorption spectrometry; Solidified floating organic drop microextraction; Slotted quartz tube; ATOMIC-ABSORPTION-SPECTROMETRY; SENSITIVE DETERMINATION; MASS-SPECTROMETRY; GRAPHITE-FURNACE; TRACE AMOUNT; LEAD; PRECONCENTRATION; COPPER; TIN; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources